نـظرات مقاصـديـة شرعيـة في أحـكام زكاة الفطـر Aspects of Maqasid al-Shari‘ah in Zakat al-Fitr - (Mohamed El-Mesawi), محمد الطاهر الميساوي; (Uthman Gurgudoo), عثمـان بن إبراهيـم غُرغُدو (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
الملخّص يهدف هذا البحث لإبراز مقاصد الشريعة من أحكام زكاة الفطر. وقد تناول فيه الباحث تعريف مقاصد الشريعة، وتعريف زكاة الفطر، وبيان حكمها التكليفي، والحكمة من مشروعيتها، ثم قام باستعراض الجوانب المهمة من مقاصد الشريعة التي يمكن إدراكها من أبرز أحكام زكاة الفطر، (نِصابِها، ووقت إخراجها، وما يتم به إخراجها، والمستحقين لها، ونقلها من بلد إلى آخر). وقد كشفت هذه الدراسة عن مصالح كثيرة تحصل للعباد، ومفاسد كثيرة تدرأ عنهم، طالما حظيت هذه الأحكام بالتطبيق على الوجه اللائق الصحيح. الكلمات المفتاحية: زكاة الفطر، مقاصد الشريعة، الحكمة، نصاب، مصالح. **************************************** Abstract This research aims at unraveling the higher objectives of Islamic law in legislating the ZakÉt al-FiÏr. The researcher defined the concept of MaqÉÎid al-SharÊ‘ah, the ZakÉt al-FiÏr, details of the obligatory nature of ZakÉt al-FiÏr and the wisdom behind its legislation. This was followed by study of the significant aspects of MaqÉÎid al-SharÊ‘ah that could be perceived from the legislation of ZakÉt al-FiÏr. This comprises its certain-minimum (niÎÉb), the time of giving it out, the conditions that must be fulfilled, the beneficiaries and its transferability from one location to another. The research discovered the benefits that are actualized for the people and the harms that are repelled from them, provided that these rules are well implemented in line with the SharÊ‘ah. Key words: ZakÉt al-FiÏr, MaqÉÎid al-SharÊ‘ah, Wisdom, Certain Minimum, Interests.